Dakwah Kultural melalui Tradisi Walimatul Aqiqah: Studi Komunikasi Simbolik pada Masyarakat Lampung - Nurcahyono, Wahyu; Nasution, Nadya Amalia; Rojiati, Umi; Frasetya, Vito (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This study aims to reveal the symbols and meanings in the walimatul aqiqah tradition and understand the role of symbolic communication in strengthening Islamic values in the community of Sukajaya Village, Tanggamus Regency, Lampung. The location was chosen because it still maintains a tradition that combines Islamic values and local Lampung culture. The study used a qualitative descriptive method with a symbolic interaction theory approach that focuses on the analysis of meaning and interpretation of symbols in social life. Data collection techniques through interviews, observations, and documentation. The data sources include primary data sources, namely one Lampung traditional figure and one religious figure and three heads of families who carry out the walimatul aqiqah tradition. The results of the study showed that symbols such as marhaban, spinning seven times, prayer, tapis cloth, baby hair shaving, candles, coconuts, flowers, baby naming, egg flowers and money, have deep meanings in strengthening Islamic values including faith, worship, morals, and sharia. Community behavior shows a harmonious integration between local Lampung culture and Islamic teachings that strengthen Islamic identity.